Forming national unity among the national service program (MNSP) participant through the language and literature program (LLP) - Chew, F.P.; Lau, P.L. (2011)
The aim of this study is to examine whether the Language and Literature Program (LLP) is effective in fostering the understanding and national unity among the various ethnic groups of National Service Program (MNSP) participants in Malaysia through the national literature mechanism. There are characteristics of literature on the ethnic group's relationship in the anthology of poems, My Motherland (2005), the mandatory text book for the participants. Quantitative method was applied by using a questionnaire to survey the acceptance of the MNSP participants toward the above anthology. Three National Service camps selected for this study represented three zones of Malaysia with 393 sample size. The Literary Unity Theory (Chew, 2007) was applied in this study and identified 13 unity indices in the anthology of poems, My Motherland (2005). Five social background characteristics of the respondents, consisted of ethnic type, gender, SES, domicile and the level of education, were analyzed regarding their relationship to the perception and the thinking of the MNSP participants. Findings showed that there were significant differences of opinions according to ethnic, SES and domicile, but no significant relationships for gender and levels of education. The impact of reading the anthology of poems, My Motherland (2005) among the MNSP participants was 21.3%. In conclusion, that MNSP was successful in building understanding among the different ethnic groups.